(3HhQUI GdGhQGb GdeGdjI (B:s (3ehbYgG ef GdGShGb (B- (3GMhGdgG heSJbHdgG (B/s - (3Rhjd, eMehO Gejfs ((3GdGScfOQjI(B: s (3OGQ GdhaGA dOfjG GdWHGYI hGdfTQ(B, s, 2000)
(3gPG GdcJGH jYQV eaghe GdHhQUI cShK eGd hGdaQb HjfgG hShb GdfbO hCfhGY GdUchc ehVY GdJYGed aj GdHhQUI , heYfi GdeVGQHI hCfhGYgG hCgOGagG hcjajI Jchjf eMaXI ChQGb eGdjI eJhGRfI hGOGQI eMGaX GdGhQGb GdeGdjI hjYQV GdeDKQGJ hcjajI GYOGOgG heYfGgG eY GdGTGQI Edi eDTQGJ GdHhQUI GdeUQjI hGdeDTQGJ GdHhQUGJ YGdjI GdcaGAI eKd HhQUGJ dfOf hHGQjS hWhcjh hfjhjhQc hjJYQV dGShGb GdeSJbHdjGJ (Bforward markets (3HfhYjgG YbhO GdNjGQGJ (Boption (3GdYbhO GdedReI (Bfuture (3aj Jdc GdGShGb , ceG jYQV GdcJGH GdeDKQGJ Ydi CSYGQ GdHhQUI hjTQM CSHGH gHhW CSYGQ GdHhQUI aj eUQ ceG jYQL Ydi SHd GdGQJaGY HeSJhi caGAI GdHhQUI GdeUQjI heSJbHd GdHhQUI GdeUQj aj Xd GdYhdeI eY GdGTGQI Edi GdHhQUI GdGhQhHjI GdeJMOI hUfGOjb GdGSJKeGQ GdYGdejI hGfYcGSGJgG Ydi GdHhQUI GdeUQjI (B.s
(3HjHdjhZQGajG U(B.137-139s
Keywords: (3GdGSges; (3GdGhQGb GdeGdjIs; (3GdHhQUGJs